Pretty things : [large type] a novel - Brown, Janelle (Thorndike Press large print core series., 2020)
"Nina once bought into the idea that her fancy liberal arts degree would lead to a fulfilling career. When that dream crashed, she turned to stealing from rich kids in L.A. alongside her wily Irish boyfriend, Lachlan. But when her mom gets sick, Nina puts everything on the line to help her, even if it means running her most audacious, dangerous scam yet. Vanessa is a privileged young heiress who wanted to make her mark in the world. Instead she becomes an Instagram influencer. But behind the covetable façade is a life marked by tragedy. After a broken engagement, Vanessa retreats to her family's sprawling mountain estate, Stonehaven. Nina, Vanessa, and Lachlan's paths collide here, on the cold shores of Lake Tahoe, where their intertwined lives give way to a winter of aspiration and desire, duplicity and revenge"--